MORAL VALUES AND THEIR DISTINCTIVE ASPECTS IN POSTMODERN SOCIETY (Scientific journal of the Fergana State University, 2025)
This article explores the theoretical foundations for researching the dialectics of changes in moral values within postmodern society from a socio-philosophical perspective. It provides a dialectical analysis of the changes in moral values in postmodern society, examines the formation of moral values, and discusses the future prospects for approaching this topic. Additionally, it analyzes the distinctive aspects of moral values in postmodern society.